Social Reform in Land Acquisition and Ownership Using Blockchain Technology Based Authorization - Yadav, Anuj; Maurya, Anant; Singh, Ashutosh; Pandey, Dilkeshwar; Kumar, Sanjeev (International Journal of Psychosocial Rehabilitation, 2020)
Digitize land and real estate this is our motto to build this project. Because as we all know in India buying and selling of land is a very hectic task and if somehow anyone finds the right property, it’s not easy to verify all details about the land like currently pending bills, right owner and need of middle man. If anyone gets success in the above-mentioned hurdles, after all this they must go through the time-consuming and paper-based land registration process. Now, if we replace the current running model by our project. After registering all the lands and real-estate properties on our platform, it is time-consuming work, but this small effort changes all aspects of buying and selling of the land. We provide dashboards for different usage; peer dashboard helps to give ownership and transfer property using the biometric system. Just one punch and all done. User dashboard for the public to manage their family and land records, giving power to the user they can list their property for sale and all the individual registered on the platform easily look for the property anywhere they want and they can also directly contact the right owner and move forward without any worries. Our system forming a family tree which helps to distribute property among the child without any type of dispute and all get legal authorization in no time. This project builds on blockchain technology that gives extra security, trust, and immutable state of the asset. The complete process requires no effort and no time, act by just a click.